Surgical Management of Manifest Exotropia and Its Effect on Cosmetic Appearance in Amblyopic Patients - Imelda, Eva; Mahfiza, Cut Salsabila; Fadliyani, Eka; Toshnowal, Nikhil (Grimsa Journal of Science Engineering and Technology, 2026)
Constant exotropia, defined by persistent outward deviation of the eye, can cause cosmetic concerns and disrupt binocular function if untreated. We report a case of a 26-year-old male with long-standing left-eye exotropia and amblyopia since early childhood. Preoperative assessment revealed a visual acuity of 6/30 in the left eye, 15° exotropia on Hirschberg testing, 30 prism diopters on prism alternate cover testing, alternating fixation with right-eye dominance, and left-eye suppression on the Worth Four Dot test. The patient underwent unilateral lateral rectus recession and medial rectus resection. One week postoperatively, ocular alignment was orthotropic with satisfactory cosmetic and motor outcomes, while functional binocular vision remained limited. This case demonstrates the effectiveness of surgical intervention in restoring alignment and appearance in adult sensory exotropia and emphasizes the importance of early detection and timely management to prevent irreversible sensory deficits.